PERHITUNGAN STRUKTUR RENCANA GEDUNG KANTOR PELAYANAN PERBENDAHARAAN NEGARA KOTA SAMARINDA PROVINSI KALIMANTAN TIMUR - PALIMBUNGA, YACOBUS (KURVA S JURNAL MAHASISWA, 2017)
With the many of development in various regions especially in the area of Samarinda about facilities and infrastructure to support the daily needs like a buildings,the bridge,and the other. The building is a place that many used for the human activity,for example is office buildings.Therefore,will be plan an office building and that is the State Treasury Services Office Of Samarinda, East Kalimantan Province , this development is because the building has been a fire incident some time ago.Analysis of Reinforced Concrete Structure on the building of State Treasury Services Office Of Samarinda, East Kalimantan Province is analyzed based on the existing data to be re-planned into nine floors with two methods namely MATRIC AND SAP 2000 with the aim to know what loads work in the structure, how the process of analysis structure and how the calculation of reinforced concrete on the building structure.